Vídeo educativo : atividades de autocuidado para prevenção de complicações nos pés de pessoas idosas com diabetes - Siqueira, Raquel dos Santos Vieira (2023)
Introduction: Population growth and changes resulting from the aging process contribute to the increase of non-communicable chronic diseases such as diabetes. Diabetes mellitus is a condition that can result in consequences such as complications to the diabetic foot, hospitalizations and even amputation of lower limbs, which increases morbidity and mortality among the elderly. For this reason, nurses play a relevant role in health education actions aimed at promoting health, preventing disease and its consequences. Objective: To build an educational video about self-care activities to prevent complications in the feet of elderly people with diabetes. Method: This is a methodological study, carried out in two stages – an integrative review of daily self-care activities that can prevent complications in the feet of elderly people living with diabetes; - construction and content validation of the educational video by a committee of judges. Results: The literature review resulted in 16 articles, which pointed out as main evidence in the prevention of complications in the feet of elderly people with diabetes, the periodic evaluation of the feet by health professionals, the early detection of lesions, the use of shoes and suitable insoles and the correct drying of the feet. This evidence was the framework for the production of the educational video, which was submitted to content validation by nine judges, obtaining a general average of the CVI equal to 0.9, which resulted in an educational technology elaborated with accessible language for elderly people with diabetes , without losing the technical quality of the information. Conclusion: The educational video is an audiovisual resource that can be used in health education activities by professionals, especially nurses. It consists of an easily accessible tool that will support elderly people with diabetes in the practice of self-care, preventing foot complications, providing comfort, safety and well-being, improving their quality of life.